PENYUSUNAN SOP PENGELOLAAN LAYANAN KENAIKAN PANGKAT REGULER DAN PILIHAN PADA BKD PROVINSI SULAWESI SELATAN - Azmi, Ilima Fitri; Marendeng Timang Palin, Dian (Politeknik STIA LAN Makassar, 2023)
Promotion is a form of appreciation given to civil servants. There are several types of promotions and each type of promotion has different management procedures. This study aims to produce outputs in the form of Government Administration Standard Operating Procedures (SOP AP) for the management of regular and elective promotion services at the Regional Personnel Agency of South Sulawesi Province. The research methods used to collect data in this study are direct observation, interviews, and document reviews. The types of data collected, processed, and used to create SOP documents are qualitative and quantitative data. Before being analyzed, the data is validated using three triangulation techniques, namely methodological, data, and theory. The results of the study in the form of SOP AP for the Management of Regular and Elective Promotion Services at the BKD of South Sulawesi Province were compiled in accordance with the regulated principles and stages of SOP preparation, as well as considering the existing laws and regulations.